TANGGUNGJAWAB NEGARA PENGIRIM TERHADAP ANAK PEKERJA MIGRAN INDONESIA ILEGAL YANG TIDAK MEMILIKI DOKUMEN DI SABAH, MALAYSIA - Sandya Farhan Agustian (Kumpulan Jurnal Mahasiswa Fakultas Hukum, 2022)
Sandya Farhan Agustian, Ikaningtyas, Hikmatul Ula Fakultas Hukum Universitas Brawijaya e-mail: sandyafrhn@student.ub.ac.id ABSTRAK Tujuan penelitian ini adalah untuk menganalisis tanggungjawab negara pengirim terhadap anak pekerja migran ilegal Indonesia yang tidak memiliki dokumen di Sabah, Malaysia. Penelitian ini menggunakan pendekatan metodologi yuridis sosiologis, yang mempunyai arti bahwa penelitian ini mengkaji masalah dengan cara meneliti dari segi ilmu hukum. Penulis memperoleh data dengan cara wawancara dan akan dianalisis dengan metode deskriptif analisis. Dari hasil penelitian dengan metode di atas penulis dapat menarik kesimpulan bahwa negara memiliki tanggungjawab terhadap anak yang tidak berdokumen sama pada anak pada umum nya dan negara sudah melakukan beberapa upaya sebagai bentuk tanggungjawab nya terhadap anak PMI ilegal yang tidak berdokumen tersebut hanya saja tanggungjawab nya belum terlaksanakan secara maksimal dan negara belum bisa menjamin semua anak PMI ilegal yang tidak berdokumen hak nya terpenuhi, namun hal tersebut semakin mejadi sulit apabila terdapat kendala dalam melakukan upaya tanggungjawab. Kata Kunci: Tanggungjawab Negara, Anak PMI ilegal, Tidak berdokumen ABSTRACT This research studies the responsibility of a state regarding Indonesian illegal migrant workers’ Children with no documents in Sabah, Malaysia. This research topic departed from the increasing numbers of illegal migrant workers’ children having no access to their rights to education, legal protection, and health care from the country their parents work in. Unfortunate children who have no access to education are forced to come with their parents to work as laborers for their continuous existence. Not a few have been captured by the Malaysian police authorities because they do not have any documents, and this situation indicates that the sending state has the responsibility to give them legal protection and to open access to their rights in line with international and national laws. Departing from the above issue, this research aims to investigate: (1) What type of responsibility of the state regarding the illegal migrant workers’ children with no documents in Sabah, Malaysia? (2) how is the responsibility implemented and what impeding factors are faced by the state in holding the responsibility for the children of the migrant workers with no documents in Sabah, Malaysia? This research employed empirical-juridical methods and socio-juridical approaches, meaning that this research sees from the perspective of legal science. The data were obtained from interviews, and they were analyzed with a descriptive method. The research results conclude that the state has the responsibility for the children of the illegal migrant workers with no documents, equal to the responsibility for most Indonesian citizens. Measures regarding this responsibility have been taken by the state but they have not been optimally implemented. Moreover, the state has not been able to ensure that the rights of the children concerned are fully covered, and to guarantee this matter will become even far-fetched when there are factors hampering the implementation of the responsibility. Keywords: State Responsibility, Indonesian Illegal Migrant Workers Children, No Document